2022
DOI: 10.3389/fimmu.2022.1043827
|View full text |Cite
|
Sign up to set email alerts
|

Molecular subtypes and a prognostic model for hepatocellular carcinoma based on immune- and immunogenic cell death-related lncRNAs

Abstract: BackgroundAccumulating evidence shows that immunogenic cell death (ICD) enhances immunotherapy effectiveness. In this study, we aimed to develop a prognostic model combining ICD, immunity, and long non-coding RNA biomarkers for predicting hepatocellular carcinoma (HCC) outcomes.MethodsImmune- and immunogenic cell death-related lncRNAs (IICDLs) were identified from The Cancer Genome Atlas and Ensembl databases. IICDLs were extracted based on the results of differential expression and univariate Cox analyses and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 94 publications
0
2
0
Order By: Relevance
“…In vitro experiments have revealed that high expression of LINC01554 partially inhibits the Wnt and PI3K-Akt pathways, resulting in reduced cell invasiveness and diminished epithelialmesenchymal transition capability. Similarly, another study [21] highlighted LINC01554, along with three other RNAs (TMEM220-AS1, LINC02362, and LINC02499), as independent prognostic factors for HCC. These consistent results suggest that LINC01554 is an important potential therapeutic target.…”
Section: Discussionmentioning
confidence: 83%
“…In vitro experiments have revealed that high expression of LINC01554 partially inhibits the Wnt and PI3K-Akt pathways, resulting in reduced cell invasiveness and diminished epithelialmesenchymal transition capability. Similarly, another study [21] highlighted LINC01554, along with three other RNAs (TMEM220-AS1, LINC02362, and LINC02499), as independent prognostic factors for HCC. These consistent results suggest that LINC01554 is an important potential therapeutic target.…”
Section: Discussionmentioning
confidence: 83%
“…He et al screened 20 lncRNAs based on 33 ICD-related genes to construct a prognostic model. The model was helpful in classifying subtypes of liver cancer based on ICD-related lncRNAs and molecules, and for predicting the prognosis of patients with liver cancer and their therapeutic response to immunotherapy ( He et al, 2022 ). Ding et al screened five lncRNAs based on 34 ICD-related genes to construct a prognostic model for gastric adenocarcinoma.…”
Section: Discussionmentioning
confidence: 99%